Tāla: Features of Rhythm System in Indian Classical Music - Velička, Eirimas (Acta Orientalia Vilnensia, 2001)
The present article aims to reveal some basic features of rhythm system in Indian classical music. On the basis of such sources as Gítālaṃkara, Nāṭyaśāstra, Sañgīa-ratnākara and the historical, typological and comparative methods the author analyses the development of tāla, describes the features of the structure of rhythm cycle, and points out the typological differences of rhythm in Indian and European music. The conclusion says, that Indian tāla and measure in European music must be ascribed different types of rhythm. Although qualitative rhythm shares some common features with tāla, it should be treated as the manifestation of quantitative rhythm. This mode of rhythm formation can be set back to Ṛgveda time, and can be related with peculiarities of phonetic structure of Sanskrit. It is also typologically kindred to antique Greek music rhythm and to some archaic Lithuanian folk songs, especially work songs and songs of calendar cycle.